Speeding up the diagnosis of multidrug-resistant tuberculosis in a high-burden region with the use of a commercial line probe assay - Angela Pires Brandao; Juliana Maira Watanabe Pinhata; Rosangela Siqueira Oliveira; Vera Maria Neder Galesi; Helio Hehl Caiaffa-Filho; Lucilaine Ferrazoli (Jornal Brasileiro de Pneumologia, 2019)
ABSTRACT Objective: To evaluate the rapid diagnosis of multidrug-resistant tuberculosis, by using a commercial line probe assay for rifampicin and isoniazid detection (LPA-plus), in the routine workflow of a tuberculosis reference laboratory. Methods: The LPA-plus was prospectively evaluated on 341 isolates concurrently submitted to the automated liquid drug susceptibility testing system. Results: Among 303 phenotypically valid results, none was genotypically rifampicin false-susceptible (13/13; 100% sensitivity). Two rifampicin-susceptible isolates harboured rpoB mutations (288/290; 99.3% specificity) which, however, were non-resistance-conferring mutations. LPA-plus missed three isoniazid-resistant isolates (23/26; 88.5% sensitivity) and detected all isoniazid-susceptible isolates (277/277; 100% specificity). Among the 38 (11%) invalid phenotypic results, LPA-plus identified 31 rifampicin- and isoniazid-susceptible isolates, one isoniazid-resistant and six as non-Mycobacterium tuberculosis complex. Conclusions: LPA-plus showed excellent agreement (≥91%) and accuracy (≥99%). Implementing LPA-plus in our setting can speed up the diagnosis of multidrug-resistant tuberculosis, yield a significantly higher number of valid results than phenotypic drug susceptibility testing and provide further information on the drug-resistance level.